Risk governance in an age of wicked problems: lessons from the European approach to indirect land-use change - Palmer, J (Routledge, 2011)
This paper assesses the recent European governance of risks associated with indirect land-use change (ILUC) arising from biofuel production. Deploying the theoretical concepts of ‘wicked problems’, ‘incertitudes’ and ‘co-production’, it argues that Europe’s existing risk governance apparatus has systematically failed to acknowledge the inherent difficulties of both identifying and interpreting knowledge pertaining to this issue, thereby sanctioning a risk management strategy that is both cognitively and democratically illegitimate. In short, existing modes of risk governance have assumed that the questions ‘what makes ILUC problematic?’ and ‘how problematic is ILUC?’ are both resolvable through objective, scientific risk assessments, when in fact they are not. This paper’s first contribution is to outline the precise characteristics of ILUC that serve to render it a wicked problem, focusing in particular on the epistemological hurdles facing those who seek to answer the two key questions outlined above. Its second contribution is then to assess the appropriateness of those science-policy relationships which have thus far been cultivated in Europe as part of attempts to deal with this issue. Specifically here, the reification of ‘ILUC factors’ as the dominant metric of ILUC risk assessment is argued to have comprised a classic instance of ‘co-production’, leading to the systematic ‘closing down’ of broader political debates around the issue. The paper concludes by contending that Europe’s risk governance apparatus will have to strive to be more inclusive, transparent, adaptable and reflexive in the future, particularly given the increasing prominence today of such multi-dimensional ‘wicked’ problems, both in the environmental sphere and beyond.